Infection by Leishmania (Leishmania) infantum chagasi causes intestinal changes B‐1 cells dependent. (19th August 2019) - Souza, Karine Delgado; Fernandes, Ellenn Pollyanna Alexandre; dos Santos, Amanda Gubert Alves; de Lima, Lainy Leiny; Gonzaga, Wagner Francisco Kennerly Marcondes; Xander, Patricia; Nogueira‐Melo, Gessilda de Alcantara; Sant'Ana, Débora de Mello Gonçales
Abstract: Evaluating the histopathological and morphometric changes caused by Leishmania (Leishmania) infantum chagasi infection either in the presence or absence of B‐1 cells. Wild‐type Balb/c and XID mice were used. Half of XID mice received B‐1 cells adoptive transfer (XID + B1). Five animals from each group were infected (Balb/c I, XID I and XID + B1 I), totalizing six groups (n = 5). After 45 days of infection, the ileum was collected for histological processing and analysis. After infection, the XID animals showed an increase in the thickness of the intestinal layers, in the depth and width of the crypt and in the villi width. However, the Balb/c I group showed a reduction in almost all these parameters, whereas the villi width was increased. The villi height decreased in the infected XID animals; however, it was increased in the XID + B1 I group. Leishmania (L) infantum chagasi infection caused a decrease in the number of Paneth cells; however, their area was increased. Finally, goblet cells and enterocytes presented different change profiles among groups. This study showed that the parasite infection causes structural and histopathological alterations in the intestine. These changes might be influenced by the absence of B‐1 cells.